Experimental Therapy of HER2-Expressing Xenografts Using the Second-Generation HER2-Targeting Affibody Molecule 188Re-ZHER2:41071 - Yongsheng Liu; Anzhelika Vorobyeva; Anna Orlova; Mark W. Konijnenberg; Tianqi Xu; Olga Bragina; Annika Loftenius; Erica Rosander; Fredrik Y. Frejd; Vladimir Tolmachev (MDPI AG, 2022)
HER2-targeted radionuclide therapy might be helpful for the treatment of breast, gastric, and ovarian cancers which have developed resistance to antibody and antibody-drug conjugate-based therapies despite preserved high HER2-expression. Affibody molecules are small targeting proteins based on a non-immunoglobulin scaffold. The goal of this study was to test in an animal model a hypothesis that the second-generation HER2-targeting Affibody molecule 188Re-ZHER2:41071 might be useful for treatment of HER2-expressing malignant tumors. ZHER2:41071 was efficiently labeled with a beta-emitting radionuclide rhenium-188 (188Re). 188Re-ZHER2:41071 demonstrated preserved specificity and high affinity (KD = 5 ± 3 pM) of binding to HER2-expressing cells. In vivo studies demonstrated rapid washout of 188Re from kidneys. The uptake in HER2-expressing SKOV-3 xenografts was HER2-specific and significantly exceeded the renal uptake 4 h after injection and later. The median survival of mice, which were treated by three injections of 16 MBq 188Re-ZHER2:41071 was 68 days, which was significantly longer (<0.0001 in the log-rank Mantel-Cox test) than survival of mice in the control groups treated with vehicle (29 days) or unlabeled ZHER2:41071 (27.5 days). In conclusion, the experimental radionuclide therapy using 188Re-ZHER2:41071 enabled enhancement of survival of mice with human tumors without toxicity to the kidneys, which is the critical organ.